2009
DOI: 10.1111/j.1745-4557.2009.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Sensory Quality of Ready‐to‐bake Chapatti During Frozen Storage

Abstract: The effect of prolonged frozen storage at −18C, on the textural and sensory properties of ready‐to‐bake frozen chapatti (R‐BFC) was evaluated. The R‐BFC samples were prepared from normal‐ (control) and microwave‐treated (18% moisture content for 80 s) wheat grains. Results showed that the extensibility of dough and maximum load for resistance increased gradually in both the samples during frozen storage; however, the increase was lesser in the treated ones. Chapattis prepared from both R‐BFC samples exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
3
9
1
Order By: Relevance
“…They also reported that addition of CMC, k‐carragenan and locust bean gum increased the maximum resistance of extension in yeasted dough as compared with control (without gum) samples. Earlier, we (Yadav et al. , 2007a,b) observed an increase in dough (non‐yeasted) extensibility during continuous frozen storage up to 6 months, but in this study it was observed that extensibility increased slightly at first freeze–thaw cycle, thereafter it continuously showed a decreasing trend.…”
Section: Resultscontrasting
confidence: 55%
See 3 more Smart Citations
“…They also reported that addition of CMC, k‐carragenan and locust bean gum increased the maximum resistance of extension in yeasted dough as compared with control (without gum) samples. Earlier, we (Yadav et al. , 2007a,b) observed an increase in dough (non‐yeasted) extensibility during continuous frozen storage up to 6 months, but in this study it was observed that extensibility increased slightly at first freeze–thaw cycle, thereafter it continuously showed a decreasing trend.…”
Section: Resultscontrasting
confidence: 55%
“…Generally lightness (L) value decreases continuously in dough during storage, but in our study we have used the flour samples, which was obtained from microwave treated wheat grains. The microwave treatment of wheat grains reduces the PPO activity in resultant flour, retarding the dough disclouration during storage (Yadav et al. , 2007a); hence less change in colour values of R‐BFC samples were observed in this study.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Flat bread samples were presented on a white paper labeled with random alphabet to the sensory panelists which were asked to evaluate the sensory attributes of the samples and rate each attribute. A nine-point hedonic scale with 1 that stands for "extremely disliking", 9 stands for "like extremely" and 5 stands for "neither like nor dislike", was used (Yadav et al, 2009).…”
Section: Sensory Analysismentioning
confidence: 99%